Majeed Amjad: A Great Poet of Nature - Malik Ghulam Hussain Arshad (بازیافت, 2017)
Majeed Amjad possesses a distinguished rank among the modern Urdu poets. He has set new trends for the contemporary Urdu verse. He has unbounding love for the world of Nature---flowers, trees, greenery, brids, crops, cascades and lakes. A bulky portion of his versification deals with the beauties of nature, scattered around us in day to day life. He has observed the minute details of plant, bird and animal life in his suburbs with a profound keenness and penned it down with utter sincerity and affection. He is the Wordsworth of Urdu poetry as ninety-five percent of his works present/unfold the various facets and beauties of Nature. The article in hand seeks to study the love and esteem of Majeed Amjad for the world of Nature in his poetry.